Incentive popular participation and empowerment of civil society: CBH-SMT Observatory - Felicio da Costa, Angélica; Grossi Bhering, Bianca; Rached Souza, Samara; Damasceno, Aline Francisco; Gragnolati Fernandes, Maisha; Ferreira Mylonas, Gabriela; Martins Arruda, Emerson; Cunha Franca, Gilberto; Cordeiro Alves dos Santos, André (Guará Journal, 2017)
The Observatory Watershed Committee of the Sorocaba River and Middle Tiete is a University Extension Program, held at the Federal University of São Carlos - campus Sorocaba (UFSCar), aims to increase the participation of civil society in the Committee, supporting discussions in chambers technical and working groups, and includethe internal public of the University. Members of the Observatory are teachers and students of the UFSCar seeking the disclosure and dissemination of knowledge about the water situation and committee meetings with lectures, workshops and social network like Facebookand website (Observatory CBH-SMT, 2015).
Keywords: Basin committee; Sorocaba; Medium river; Water resources